2021
DOI: 10.3390/antibiotics10111325
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Carbapenem-Resistant Gram-Negative Bacilli in Patients with Ventilator-Associated Pneumonia

Abstract: Carbapenem-resistant Gram-negative bacilli (CR-GNB) has become a global threat. In hospital settings, the association of CR-GNB with ventilator-associated pneumonia (VAP) is a critical public health concern owing to their high resistance rate to most antibiotics. The present study aims to identify the frequency of carbapenem-resistance and to determine the rate of multidrug resistance (MDR), extensive drug resistance (XDR) and pan-drug resistance (PDR) among CR-GNB infections in VAP. Antimicrobial susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
4
8
1
Order By: Relevance
“…33 Concerning the type of bacteria detected in the current study, K. pneumoniae was the predominant isolate, followed by A. baumannii, P. aeruginosa and E. coli, representing 34.9%, 20.5%, 18.1% and 12%, respectively. This result was in agreement with Mohammed et al and Gajdacs et al 34,35 In contrast, greater prevalence of P. aeruginosa was detected in other studies. 36,37 Meanwhile, Chen et al, Kumari et al, and Sadigov et al reported that A. baumannii was the most prevalent CR-GNB pathogen, accounting for 78.7%, 37.4%, and 37.1%, respectively.…”
supporting
confidence: 93%
“…33 Concerning the type of bacteria detected in the current study, K. pneumoniae was the predominant isolate, followed by A. baumannii, P. aeruginosa and E. coli, representing 34.9%, 20.5%, 18.1% and 12%, respectively. This result was in agreement with Mohammed et al and Gajdacs et al 34,35 In contrast, greater prevalence of P. aeruginosa was detected in other studies. 36,37 Meanwhile, Chen et al, Kumari et al, and Sadigov et al reported that A. baumannii was the most prevalent CR-GNB pathogen, accounting for 78.7%, 37.4%, and 37.1%, respectively.…”
supporting
confidence: 93%
“…Multiplex PCR was used to detect the five significant carbapenemase-encoding genes in K. pneumoniae ( bla KPC , bla NDM , bla VIM, bla IMP , and bla OXA-48 ) [ 12 ]. A total volume of 30 µL was adequately prepared for the PCR reaction mixture, including 5 µL (100 ng) of template DNA, 15 µL of PCR master mix, and 2 µL (5 pmol) of each primer ( Table 9 ) [ 57 , 58 ]. The volume was then completed with nuclease-free water up to 30 µL.…”
Section: Methodsmentioning
confidence: 99%
“…Because they are highly resistant to most antibiotics. 33 In this study, more than half of the CAP patients had these bacteria in their etiological cultures. This means that the use of antibiotics in these groups is limited.…”
Section: Discussionmentioning
confidence: 81%